(untitled) (Global Journal of Medical Research, 2022)
Simple diagnostic imaging WHIS-RAD and ultrasound are non-available for health workers practicing in low-resource developing nations A low-tech approach rather than hi-tech is appropriate with excellent clinical results These adjuncts to the history and physical will lead to markedly improved clinical outcomes